Sexual system and molecular genetics of Anchialine shrimp species Parhippolyte uvea (Decapoda : Caridae: Barbouriidae) and Anticaridina lauensis (Decapoda : Caridae Atyidae) from the Philippines - Ebreo, Karen Claire S
Achialine pools are coastal landlocked brackish- or salt-water pools with subterranean connections to the sea. These habitats were reported from a number of limestone islands in the Philippines, including Tiniguiban and Hinlaran anchialine pools are dominated by red caridean shrimps, specifically Parhippolyte uveae Borradaile, 1900 (Barbouriidae) and Antecaridina lauensis (Edmondson, 1935) (Atyidae). The sexual system of P. uveae was examined through examination of external morphology, gonad histology and size-sex frequency distribution analysis. In addition, molecular genetics of the two anchialine shrimp species were investigated. A third, rarer shrimp species was discovered in Tiniguiban pool, and its identity was investigated using both genetic and morphological means. Results showed that the sexual system of P. uveae is protandric simultaneous hermaphroditism, where the shrimp initially reproduce as males, then as it grows, change into hermaphrodites that can reproduce as both male and female at the same time. Male phase (MP) shrimps were generally smaller, have coupling hooks (CH) and appendices masculinae (AM) on the first and second pleopods, respectively. Their gonads contain mature sperm cells along with previtellogenic oocytes. On the other hand, hermaphrodites have both male and female gonopores, and pleopod appendages were absent. Their gonads contain both mature sperm cells and vitellogenic oocytes. Transitional individuals, those with male external morphology and hermaphrodite gonad characters, were also recorded. Results on the molecular genetics analyses of both P. uveae and A. lauensis supported the hypothesis that anchialine populations have high gene flow and low genetic differentation, except if there is a strong barrier. Antecaridina lauensis population in the Visayas are comprised of three clades, potentially representing crptic species. Further morphological examination and other molecular analyses will be needed to delineate this putative species complex. The third anchialine shrimp from Tiniguiban belongs to the genus Metabetaeus (Alpheidae), which is the first record of the genus in the Philippines.